2019
DOI: 10.1152/japplphysiol.00940.2018
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation changes induced by lower-body negative pressure in men and women

Abstract: We investigated whether lower-body negative pressure (LBNP) application leads to coagulation activation in whole blood (WB) samples in healthy men and women. Twenty-four women and 21 men, all healthy young participants, with no histories of thrombotic disorders and not on medications, were included. LBNP was commenced at −10 mmHg and increased by −10 mmHg every 5 min until a maximum of −40 mmHg. Recovery up to 10 min was also monitored. Blood samples were collected at baseline, at end of LBNP, and end of recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…We recently reported that sex differences exist in coagulation in both resting conditions and during LBNP application [ 4 ]. Specifically, women are relatively hypercoagulable compared to men during resting baseline conditions, but men show a more pronounced LBNP-induced shift towards hypercoagulability [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported that sex differences exist in coagulation in both resting conditions and during LBNP application [ 4 ]. Specifically, women are relatively hypercoagulable compared to men during resting baseline conditions, but men show a more pronounced LBNP-induced shift towards hypercoagulability [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that sex differences exist in coagulation in both resting conditions and during LBNP application [ 4 ]. Specifically, women are relatively hypercoagulable compared to men during resting baseline conditions, but men show a more pronounced LBNP-induced shift towards hypercoagulability [ 4 ]. The current study extends the above literature with the finding that respective baseline levels of FII, FVII, FVIII, PC, and PS are the same in the two phases, thus implying that the phase of the menstrual cycle does not affect coagulability during resting conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations